(untitled) (Research, Society and Development, 2021)
Our aim was to determine whether microalgae (Schizochytrium limacinum) supplementation affects daily production, composition and fatty acid profile of organic milk. Eight lactating cows were kept in pasture and divided in two groups: those fed corn cob as a supplement twice a day during milking (CTL) and those fed corn cob mixed with 100 g of microalgae (ALG) per cow daily. Microalgae did not affected daily milk production and composition, but a tendency of milk fat reduction was observed. The level of stearic acid in the milk of cows fed ALG was significantly lowered 2.46-fold, whereas levels of elaidic acid and conjugated linoleic acid were significantly elevated by 3.3-fold and 1.8-fold, respectively. A significantly greater PUFA:MUFA ratio was observed in ALG treatment, while the MUFA:saturated fatty acid ratio showed a tendency to increase (P=0.073). Microalgae rich in omega-3 fatty acids successfully enrich organic milk without negatively affecting productivity or composition. Consumers could be attract to increase the intake of omega 3 polynsaturated fat from organic milk. These results could support nutritionist and farmers decision to feed microalgae to dairy cattle since it is economically viable.